2022
DOI: 10.3390/cells11192981
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Moringa oleifera to Ameliorate HAART-Induced Pathophysiological Complications

Abstract: Highly active antiretroviral therapy (HAART) comprises a combination of two or three antiretroviral (ARV) drugs that are administered together in a single tablet. These drugs target different steps within the human immunodeficiency virus (HIV) life cycle, providing either a synergistic or additive antiviral effect; this enhances the efficiency in which viral replication is suppressed. HIV cannot be completely eliminated, making HAART a lifetime treatment. With long-term HAART usage, an increasing number of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 151 publications
0
1
0
Order By: Relevance
“…However, oxidative stress leads to NRF2 dissociation from KEAP1, enabling NRF2 accumulation and phosphorylation in the cytoplasm. Phosphorylated NRF2 then translocates to the nucleus where it dimerizes with small Maf proteins and recognizes ARE sequences, promoting the transcription of antioxidant genes, such as HO-1 and SOD [37]. One study revealed that extraordinary intensities of oxidative stress led to NRF2 downregulation [38].…”
Section: Discussionmentioning
confidence: 99%
“…However, oxidative stress leads to NRF2 dissociation from KEAP1, enabling NRF2 accumulation and phosphorylation in the cytoplasm. Phosphorylated NRF2 then translocates to the nucleus where it dimerizes with small Maf proteins and recognizes ARE sequences, promoting the transcription of antioxidant genes, such as HO-1 and SOD [37]. One study revealed that extraordinary intensities of oxidative stress led to NRF2 downregulation [38].…”
Section: Discussionmentioning
confidence: 99%